2017
DOI: 10.1016/j.physbeh.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility or resilience? Prenatal stress predisposes male rats to social subordination, but facilitates adaptation to subordinate status

Abstract: Mood disorders such as major depressive disorder (MDD) affect a significant proportion of the population. Although progress has been made in the development of therapeutics, a large number of individuals do not attain full remission of symptoms and adverse side effects affect treatment compliance for some. In order to develop new therapies, there is a push for new models that better reflect the multiple risk factors that likely contribute to the development of depressive illness. We hypothesized that early lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Our results suggest that animals that were relocated while in utero may actually be more resilient when later dealing with challenge. This interpretation would be consistent with a prenatal stress inoculation effect, consistent with some human and animal studies (DiPietro et al, 2006;Ehrlich and Rainnie, 2015;Scott et al, 2017;Serpeloni et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results suggest that animals that were relocated while in utero may actually be more resilient when later dealing with challenge. This interpretation would be consistent with a prenatal stress inoculation effect, consistent with some human and animal studies (DiPietro et al, 2006;Ehrlich and Rainnie, 2015;Scott et al, 2017;Serpeloni et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…DiPietro et al ( 2006 ) showed that mild to moderate amounts of perceived stress and anxiety by the mother during pregnancy were associated with more advanced mental and motor development in human children at 2 years of age. A more recent report showed that prenatal stress may confer a protective phenotype, buffering animals against future stressors (Scott et al, 2017 ). Pregnant female mice were exposed to a series of chronic variable stressors during their last week of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as the auditory system becomes active between PND7 and PND15 (de Villers-Sidani et al, 2008; Säljö et al, 2011), it could be postulated that more immature animals could be refractory to the damaging effects of noise on this type of memory, probably due to the impossibility of noise to affect CNS by means of a functional auditory system. As no effect was observed when PND15 animals were exposed to noise for 5 days, it could be suggested that repeated exposures might trigger adaptive mechanisms intended to counteract potential damage (Febbraro et al, 2017; Scott et al, 2017). The ability of EE to prevent noise-induced changes in PND15N1 animals might depend on the same adaptive mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Although all animals retained associative memory in this task, the performance in the associative memory task was increased in rats exposed at PND7N5 and PND15N1, suggesting that these animals would have a more detailed representation of the traumatic event, as reported by Atucha and Roozendaal (2015). Again, the lack of change in the other groups might be related to either immature associative mechanisms (PND7N1) or to adaptive mechanisms (PND15N5) that could be triggered by repeated exposures, intended to counteract potential damage, as observed in different stress models (Febbraro et al, 2017; Scott et al, 2017). However, as memory retention has been observed in both groups, it should not be discarded that PND7N5 and PND15N1 rats experimented an increase in fear sense instead of an improvement in associative memory (i.e., there seems not to be a memory acquisition trouble).…”
Section: Discussionmentioning
confidence: 99%
“…Results from our study raises the intriguing question of whether the methylation differences are associated with alterations in neurodevelopment and stress response in the infants. Studies of prenatal stress in animals show mixed behavioral outcomes in terms of resilience, with one showing resilience in females only (Zuena et al, 2008) and another showing males becoming predisposed but better adapted to subordinate status (Scott et al, 2017). Unfortunately, there is no information available on any stress-related outcomes, mental or physical health, or sex of the BBC infants.…”
Section: Discussionmentioning
confidence: 99%